Factors influencing the intention to watch online video advertising among UiTM Kampus Bandaraya Melaka student / Faris Ahmad Anis Ahmad - Anis Ahmad, Faris Ahmad (Faculty of Business and Management, 2018)
The purpose of this study is to identify the factors influencing the intention to watch online video advertising among UiTM Kampus Bandaraya Melaka student. The research is based on a sample of 274 respondents. The results show that attitude toward watching OVA, subjective norm and past watching of OVA have significant influence on intention to watch OVA among UiTM Kampus Bandaraya Melaka student. It involve the process of conducting the research such as in determining the sample, the reliability and validity of questionnaire and including the research design, sampling technique, data collection method also involving primary data, secondary source and data analysis technique. Online video advertising (OVA) is a new forms of advertising which is growing extremely well in recent years and it could generate a large amount of revenue as compared to traditional advertising and it is much lower in cost as compared to other advertising platform. The main objectives of this study is to investigate whether factors (ie: attitude toward watching OVA, subjective norm and past watching of OVA) have impact on influencing the intention of UiTM Kampus Bandaraya Melaka student to watch online video advertising and also to identify the most influential factor that influence the intention of UiTM Kampus Bandaraya Melaka student to watch online video advertising. The strongest relationship is between subjective norm and intention to watch online video advertising.